Influence of Pricing Strategy on Microinsurance Uptake among Micro and Small Enterprises in Nairobi City County, Kenya - Mulumbi, Aggrey; Onjure, Caleb; Muriithi, Jane (International Journal of Strategic Management, 2025)
Purpose: The study aimed to investigate influence of pricing strategy on microinsurance uptake among micro and small enterprises in Nairobi County, Kenya. Methodology: The study used a descriptive research methodology and positivist perspective. From a population of 12,429 registered MSEs in Nairobi County, a representative sample of 387 MSEs was chosen by multistage random selection. Structured questionnaires were used in data collecting; a pilot test was done to guarantee dependability and validity. SPSS version 27 let one examine quantitative data. While inferential analysis used several regression and correlation strategies to assess hypotheses at a 95% confidence level (p < 0.05), descriptive statistics including means and standard deviations were computed. Findings: Strong positive associations between microinsurance adoption and pricing techniques were found by the study (r = 0.672), notably at p < 0.01. Regression models revealed that pricing explained 45.2% of the microinsurance adoption variation. The ANOVA findings show an F-statistic of 247.449 with a p-value of 0.000 further indicating that the association between microinsurance acceptance and pricing strategy approach was statistically significant at the 95% confidence level. With an unstandardized coefficient (B) for the pricing strategy of 0.409, one unit increase in the pricing strategy resulted in 0.409 units rise in microinsurance adoption. Unique Contribution to Theory, Practice and Policy: The study therefore recommended that microinsurance providers should implement flexible pricing structures tailored to the financial realities of MSEs. This includes staggered payment plans, seasonal premium adjustments, income-based premiums, and loyalty discounts. Additionally, transparent communication of costs and benefits must accompany any pricing model to enable informed decision-making by businesses.